Interaction between Vitamin D homeostasis, gut microbiota, and central precocious puberty - Guo, Doudou; Ning, Xin; Bai, Tao; Tan, Lingfang; Zhou, Yanfen; Guo, Zhichen; Li, Xin (Frontiers in Endocrinology, 2024)
Central precocious puberty (CPP) is an endocrine disease in children, characterized by rapid genital development and secondary sexual characteristics before the age of eight in girls and nine in boys. The premature activation of the hypothalamic-pituitary-gonadal axis (HPGA) limits the height of patients in adulthood and is associated with a higher risk of breast cancer. How to prevent and improve the prognosis of CPP is an important problem.Vitamin D receptor (VDR) is widely expressed in the reproductive system, participates in the synthesis and function of regulatory sex hormones, and affects the development and function of gonads. In addition, gut microbiota plays an important role in human health by mainly regulating metabolites, energy homeostasis, and hormone regulation. This review aims to clarify the effect of vitamin D deficiency on the occurrence and development of CPP and explore the role of gut microbiota in it. Although evidence on the interaction between vitamin D deficiency, gut microbiota, and sexual development remains limited, vitamin D supplementation and gut microbiota interventions offer a promising, non-invasive strategy for managing CPP.